Halal Product Assurance: Review of Regulatory Effectiveness and Legal Protection for Consumers and Business Actors - Rizqi Khoirunisa; Shohib Muslim; Farida Akbarina; Ikhsan Setiawan (JBS Nexus, 2024)
Halal has become a major concern for Muslims, especially among the Indonesian population. The halal status of a food is determined by its nature and the methods used to obtain and maintain it. This research aims to find out how effective the implementation of halal product guarantee certification arrangements is for business actors and how legal protection is for consumers in guaranteeing halal products. This research uses literature study. This research process includes collecting library data, reading, taking notes, studying, and collecting ideas or manuscripts. After that, the collected data or text is described and explained according to the research topic. The research results show that there is still a lack of awareness among business actors regarding the requirement for companies that produce goods from non-halal materials to disclose non-halal information on their products. Available information regarding halal product certification is still limited, although knowledge on the topic is considerable. Stricter regulations are needed for non-halal food products because the number of halal ingredients is greater than for non-halal food products. This type of reasoning also applies in the legal field. Halal certificates and halal labels are used to protect consumers’ rights to obtain the products of their choice. In particular, to avoid things that involve using substances or engaging in practices that are prohibited by religious beliefs. To guarantee the use of halal products, governments may implement various measures in addition to requiring halal certification. Buyers must always have knowledge about halal and non-halal food products. Ensuring safety and self-confidence is very important for clients, especially those who follow the Islamic fait